Methodology to buidling a pipeline of economically and environmentally sustainable business models - Hientz, Lennart; Masika, Daniel; Wamicwe, Peter; Newman, Richard; Grosjean, Godefroy; Derenoncourt, Marie Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report elaborates on the methodology to source and screen a pipeline of high CSA impact economically and environmentally sustainable business models (SMEs) from diverse sources, prioritizing women-led SMEs, in Africa that can be linked to innovative investment solutions.